Urban Modes of Assemblage: The Changing Spaces of Innovation in Shanghai - Renaud, Clément; Fernandez, Valerie; Puel, Gilles; Feng, Zhen (Management international / International Management / Gestiòn Internacional, 2019)
The present article considers the evolution of relationships between four organizations located in Shanghai (two coworking spaces, a hackerspace and a public network of spaces dedicated to education) between the years 2011 and 2015. We start by describing how Shanghai’s urban policies lead to the development of vast real estate that failed at supporting smaller and less formal initiatives. Drawing from previous research and fieldwork, we show how groups of individuals started to organize with the goal of defining new spaces for discussions and activities around technological innovation and entrepreneurship. For each of the four organizations selected, we give a detailed account of their spatial and organizational developments over time, and how they relate to each other. We propose what we called “modes of assemblage” to understand how discrete and partial associations between them helped to change Shanghai’s discourse and positioning about innovation, prefiguring major national programs.